Species-cum-provenance Trial of Eucalyptus in Dry Zone of Maharashtra - Jha, Mohan (Indian Forester, 1991)
A species-cum-provenance trial of Eucalyptus was undertaken at Forest Research Centre, Jalna under rainfed condition without any addition of fertilizer. Data collected 3 years after planting has been analysed for survival percentage, height and girth Eucalyptus tereticornis provenance Kennedy River has produced tbe best average height and Eucalyptus carnaldulensis provenance East Leichardt River bas shown the best average girth.